THE EFFECT OF SERVICE QUALITY AND TRUST ON THE DECISION TO USE MANDIRI M-BANKING IN SOUTH JAKARTA - Muhammad Bagas Wicaksono (2021)
This study uses a quantitative descriptive method that is carried out on the decision to use Mandiri mobile banking in South Jakarta. The purpose of this study was to determine the effect of trust and service quality on the decision to use Bank Mandiri mobile banking. The sample in this study were Bank Mandiri mobile banking users in South Jakarta. The sample size is 50 respondents. The sampling method is non-probability sampling and the sampling technique is purposive sampling. This study uses data from a collection of questionnaires. The data analysis in this study is the partial least square (PLS) analysis method with the help of the SmartPLS 3.0 software. The results showed that the trust variable had a significant and significant effect on the use decision with a path coefficient value of 0.204. Meanwhile, service quality has a significant influence on usage decisions with a path coefficient of 0.730. The R-square of the decision to use is 78.3%, which means that the contribution of trust and service quality to the decision to use is 78.3% and the remaining 21.7% is influenced by other variables, namely perceived benefits, ease of use, and price.